Surgical techniques for evacuation of chronic subdural hematoma: a mini-review - Rodriguez, Benjamin; Morgan, Isabella; Young, Tirone; Vlastos, Joseph; Williams, Tyree; Hrabarchuk, Eugene I.; Tepper, Jaden; Baker, Turner; Kellner, Christopher P.; Bederson, Joshua; Rapoport, Benjamin I. (Frontiers in Neurology, 2023)
Chronic subdural hematoma is one of the most common neurosurgical pathologies with over 160,000 cases in the United States and Europe each year. The current standard of care involves surgically evacuating the hematoma through a cranial opening, however, varied patient risk profiles, a significant recurrence rate, and increasing financial burden have sparked innovation in the field. This mini-review provides a brief overview of currently used evacuation techniques, including emerging adjuncts such as endoscopic assistance and middle meningeal artery embolization. This review synthesizes the body of available evidence on efficacy and risk profiles for each critical aspect of surgical technique in cSDH evacuation and provides insight into trends in the field and promising new technologies.